A critical evaluation and measurement of organisational readiness and adoption for continuous improvement within a medical device manufacturer. Issue 2 (3rd April 2023) - McDermott, Olivia; Antony, Jiju; Sony, Michael; Looby, Ellen
ABSTRACT: This research aims to assess the organisational readiness and maturity of continuous improvement (CI) deployment in a medical device manufacturer. A single case study approach was used, in an Irish medical device company with 500 indirect staff members. The data were collected through a quantitative survey, and results were used to provide practical measures and assessment of readiness and inform the future development of the CI initiative. This case study demonstrates that CI deployment practice is consistent with literature findings and that employee motivation, employee empowerment and employee knowledge, management commitment, CI linked to strategy and communication of CI strategy are all key enablers for sustained CI deployment and success. Despite being within a highly regulated industry, there was an overall positive culture of acceptance and embracing of CI methods and initiatives within this organisation. The study presents a practical approach to assessing organisational readiness and maturity for CI to identify areas of strength that can be used as cornerstones of an initiative and areas that would benefit from further development prior to implementation.